A multicomponent approach to thinning reinforcer delivery during noncontingent reinforcement schedules. Issue 1 (11th December 2017) - Slocum, Sarah K.; Grauerholz‐Fisher, Emma; Peters, Kerri P.; Vollmer, Timothy R.
Abstract : We evaluated a noncontingent reinforcement procedure that involved initially providing three subjects with signaled, continuous access to the functional reinforcer for aggression and slowly increasing the amount of time subjects were exposed to the signaled unavailability of the reinforcer. Additionally, alternative potential reinforcers were available throughout the sessions. Results showed immediate and substantial reductions in aggression for all three subjects. The clinical utility of this intervention is discussed, and future research directions are recommended.